Acorn Bread in Iron Age of North-western Iberia, from Gathering to Baking - Estevo Amado Rodríguez (EXARC, 2013)
Strabo's Geography is one of the main sources that archaeologists use for the study of the Castro Culture’s (Iron Age in north-western Iberia) customs on food and consumption. In his description, he affirms that during two thirds of the year, those mountaineers fed on the acorn. The archaeological evidence shows that these people were mainly farmers; therefore Strabo presents this idea of gathering and poor agriculture in an attempt to contrast Castro Culture with a civilized image of Rome. However, the gathered products would constitute an important part of their diet, as the common finding of acorns in a substantial number of settlements seems to indicate.